An in-wheel sensor for monitoring tire-terrain interaction: Development and laboratory testing. (April 2019) - Longoria, Raul G.; Brushaber, Robert; Simms, Andrew
Highlights: In-wheel sensor system for pneumatic tires has been developed and tested. System tested using a drum-test machine over a wide range of conditions. Signal processing methods and measures of tire-terrain contact developed. Validation by measurement of contact length comparing with past studies. Tire shape metrics to guide adjustment of inflation pressure on diverse terrains. Abstract: An in-wheel sensor system was developed to monitor the deflection and shape of a tire that it is operating on and interacting with terrain. Three ultrasonic sensors were mounted to rotate with the wheel rim to measure radial distance to the inner tire surface at the mid-plane and at two equidistant lateral planes of the tire. This study describes evaluation of the sensor system using a laboratory drum-test machine which drives the tire over a wide range of speeds at different normal tire loads and inflation pressures. Signal processing methods are described for extracting characteristic measures of the tire contact and shape geometry which can be determined from measurements of inner tire surface deflection. The measurement of contact length compared well with results measured using other methods and reported in the literature. Additional tire shape metrics are defined that may be useful for informing how automated adjustments can be made to inflation pressure by central tire inflation pressure systems. In most of the test cases, the three sensors showed no significant lateral variation in measured deflections, as expected for testing on a rigid drum.